Acceptance and Hesitancy of COVID 19 Vaccination Among Medical and Allied Health Students in India - A Pilot Study (International Journal of Scientific Research in Science and Technology, 2024)
Coronavirus disease 2019 (Covid-19) has had a lasting impact globally, resulting in an exponential rise in mortality and morbidity associated with it. In order to counteract this deadly disease, several Covid-19 vaccines were introduced in human trials. In the midst of lot of controversies regarding the efficacy of these vaccines, as well as the potential adverse effects experienced by the vaccinated individuals the questions of acceptance and hesitancy grew stronger. Since the medical and allied health students have access and understanding of evidence based research, their opinions would help in understanding the situation better. Hence, the aim of the present study was to learn about acceptance, hesitancy of Covid vaccination among health care students. A questionnaire-based online survey was conducted in India between 1st May 2021 and 12th July 2021. A total of 212 responses from health care students were obtained from various states. The questionnaire was circulated via social media platforms, which mainly included questions on acceptance, hesitancy, efficacy and adverse effects of vaccines available in India. Responses have been received from Maharashtra, Karnataka, Goa, Haryana, New Delhi, Chhattisgarh, Andhra Pradesh, Tamil Nadu, Kerala, Uttar Pradesh and Punjab. 61.8% of the responders were from the age group of 18-24. The review of this very important aspect is crucial which has been often neglected amidst the pandemic. This study may help in implementation of better public policies in future.